Decoding task and stimulus representations in face-responsive cortex. Issue 7 (16th November 2016) - Kliemann, Dorit; Jacoby, Nir; Anzellotti, Stefano; Saxe, Rebecca R.
ABSTRACT: Observers can deliberately attend to some aspects of a face (e.g. emotional expression) while ignoring others. How do internal goals influence representational geometry in face-responsive cortex? Participants watched videos of naturalistic dynamic faces during MRI scanning. We measured multivariate neural response patterns while participants formed an intention to attend to a facial aspect (age, or emotional valence), and then attended to that aspect, and responses to the face's emotional valence, independent of attention. Distinct patterns of response to the two tasks were found while forming the intention, in left fronto-lateral but not face-responsive regions, and while attending to the face, in almost all face-responsive regions. Emotional valence was represented in right posterior superior temporal sulcus and medial prefrontal cortex, but could not be decoded when unattended. Shifting the focus of attention thus alters cortical representation of social information, probably reflecting neural flexibility to optimally integrate goals and perceptual input.